ANALYSIS OF TEACHER STRATEGIES IN TEACHING ENGLISH USING DIFFERENTIATED LEARNING - Tri Fanny Anggraeny; Dian Novita Dewi (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research aims to analyze the teachers’ strategies for teaching English using differentiated learning. The researcher used a case study as the method. The subjects were two teachers who are the driving teacher or Guru Penggerak. Interviews and observation were utilized to collect the data. The data was analysed using triangulation. The result shows differentiated learning is the process of modifying instruction to match the needs of individual students, and as a solution to students' requirements, the teacher presents them with multiple possibilities for absorbing information it is important to implement because in one class there are various needs of the students that should be fulfilled. Strategies used by the teachers to accommodate the student's needs are from the content, process, and product. The content, process, and product should be different based on the students' needs but on the same topic. Another strategy used by the teachers to ensure the student's participation is to make the students busy with the task and the target that should be fulfilled. Thus, this research concludes that the implementation of differentiated learning in class is effective that can help the students to understand the material according to the students’ needs. For further research, the researcher might be investigated the effectiveness of differentiated learning for student outcomes and for the school, to facilitate workshops or training for the teachers about differentiated learning.